2016
DOI: 10.1038/micronano.2016.19
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of silicon-tessellated structures for monocentric imagers

Abstract: Compared with conventional planar optical image sensors, a curved focal plane array can simplify the lens design and improve the field of view. In this paper, we introduce the design and implementation of a segmented, hemispherical, CMOS-compatible silicon image plane for a 10-mm diameter spherical monocentric lens. To conform to the hemispherical focal plane of the lens, we use flexible gores that consist of arrays of spring-connected silicon hexagons. Mechanical functionality is demonstrated by assembling th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…3D presents the EQE spectrum of a photodiode. We observe EQE > 80% at λ > 650 nm, which to our knowledge is above those reported for other hemispherical imagers (5,8,22,27,32). The photodetector noise equivalent power (NEP) is NEP = ffiffiffiffiffiffiffiffiffi ffi 2qI D p =RðλÞ under shot-noise-limited detection at −1 V, where q is the electron charge, I D is the dark current, and RðλÞ is the responsivity at a given wavelength λ.…”
Section: And In Methodsmentioning
confidence: 47%
See 2 more Smart Citations
“…3D presents the EQE spectrum of a photodiode. We observe EQE > 80% at λ > 650 nm, which to our knowledge is above those reported for other hemispherical imagers (5,8,22,27,32). The photodetector noise equivalent power (NEP) is NEP = ffiffiffiffiffiffiffiffiffi ffi 2qI D p =RðλÞ under shot-noise-limited detection at −1 V, where q is the electron charge, I D is the dark current, and RðλÞ is the responsivity at a given wavelength λ.…”
Section: And In Methodsmentioning
confidence: 47%
“…to correct these aberrations that increase the complexity, weight, and cost, while often decreasing the functionality of the imaging system. Many efforts, therefore, have been made to shape the FPA into a hemisphere (1,4,5,8,19,22,(26)(27)(28)(29). Fabricating arrays on retina-like hemispherical surfaces (5,22,30,31), however, introduces significant challenges.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…i) Magnified view of the kirigami‐based device's high pixel density. Reproduced with permission . Copyright 2016, Nature Publishing Group.…”
Section: Biomimicry Of Single‐chambered Eyesmentioning
confidence: 99%
“…In this scheme, a photodetector array with an elaborate petal pattern is fabricated (Figure g, left) and then transferred to a concave hemispherical holder (Figure g, right). Recently, Wu et al reported a hemispherical Si‐based photodetector array by applying the kirigami method (Figure h) . Si of thickness <20 µm supplies material flexibility, and the tessellated hexagonal structures enable structural flexibility, both of which help form a hemispherical imager.…”
Section: Biomimicry Of Single‐chambered Eyesmentioning
confidence: 99%